Dėl senųjų raštų posesyvinių konstrukcijų su veiksmažodžiu priklausyti - Maskuliūnas, Bronius (Baltistica, 2001)
ON THE POSSESSIVE CONSTRUCTIONS WITH THE VERB priklausyti ‘TO BELONG’ IN OLD LITHUANIAN WRITINGSThe paper discusses the possessive constructions with the verb priklausyti ‘to belong’ in Old Lithuanian writings. Possessive dative constructions with the verb priklausyti compete not with analogical adessive, but with allative constructions. This confirms the view that the neutralisation of allative and adessive constructions took place in the 16th–17th c. The alternation of possessive dative constructions with the preposition prieg encountered in old records is a related phenomenon. The analysis of possessive constructions indicates that in Lithuanian written records of the 16th–17th c. not only the adessive positional construction prieg + dative was used, but also the construction prieg + genitive correlating with the allative case was still used with verbs.